"A2 milk" authentication using isoelectric focusing and different PCR techniques. (September 2021) - Mayer, Helmut K.; Lenz, Kathrin; Halbauer, Eva-Maria
Graphical abstract: Highlights: Milk protein polymorphism and "A1/A2 hypothesis" (β-caseins) are highlighted. Phenotyping of genetic variants of milk proteins in Simmental cows ( n = 568) by IEF. Genotyping of β-caseins variants by AS-PCR, ACRS-PCR, and PCR-RFLP techniques. Detection of β-casein A1 in retail "A2 milk" is a deception/misleading of consumers. Abstract: Genetic variants of milk proteins have attracted great interest for decades as they are related to important issues such as the composition and technological properties of milk. More recently, an "A1/A2 hypothesis" was developed saying that β-casein variant A1 may be a dietary risk factor for cardiovascular diseases, type 1 diabetes, sudden infant death syndrome and neurological disorders due to the release of β-casomorphin-7, whereas no evidence for such adverse effects was assumed for β-casein A2. Thus, the aim of this study was to adapt and establish analytical methods for the identification of genetic variants of β-casein using isoelectric focusing of milk proteins as well as appropriate PCR techniques. Allele-specific polymerase chain reaction (AS-PCR) proved to be a reliable method for differentiating most common β-casein variants (A1, A2, B, C), amplification-created restriction site (ACRS)-PCR using three different restriction enzymes allowed also the detection of variant A3, and the restriction fragment length polymorphism (RFLP)-PCR method enabled the reliable discrimination between A2 (homozygote/heterozygote) and non-A2 animals. Since traces of β-casein A1 were also found in commercial "A2 milk" in Austria, the authentication of such expensive dairy products is urgently recommended, both by genotyping of all dairy cows at farm level (to confirm that all cows are homozygous β-casein A2A2) and by screening commercial products on the market (to confirm the absence of β-casein variants A1, B, and C in dairy products labelled "A2 milk") to protect consumers from this unexpected fraud.